Implementasi Teknologi Air Cooler kepada Karang Taruna Desa Banjarsari - Tholib Hariono; Hilyah Ashoumi; Sujono Sujono (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
The objectives of the community service activities in this scheme with the name of the Implementation of Appropriate Technology for air coolers are: First, to hone the skills of the youth. Second, Encouraging interest in youth talent in the field of technology. This service uses the service learning method which is one approach in teaching, combining academic goals and efforts to raise awareness in solving problems directly. With the socialization of making a simple Air Cooler using this Peltier, youth who are members of the Karang Taruna organization in Banjarsari Village can understand technology. In the implementation of this service, the response given by the youth of Banjarsari Village was very good with a percentage of 88.2% being satisfied. They were very enthusiastic in participating in these activities with the acquisition of 94.1% willing to immediately practice the results of service.